Building Sustainable Futures: Developing a Halal Supply Chain Leadership Competency Framework - Voak, Adam; Fairman, Brian; Helmy, Abdullah (el-Jizya : Jurnal Ekonomi Islam, 2024)
This paper presents some reflective perceptions of the current issues and the future challenges facing the Halal supply chain sector. Of particular concern is the challenge of attracting suitable talent to sustain its fast growth and developing future leaders to ensure that cross-border interactions remain culturally safe and respectful. Whilst it is agreed that much work has begun in establishing technical Halal competence within supply chains (Abd Rahman, Abd Mubin, Yusof, & Kamarulzaman, 2021; Hashim & Shariff, 2016), there remains a dearth of discussion around the design and development of a leadership framework to ensure its ongoing sustainability. In this respect, current knowledge around leadership in the Halal diaspora appears to consist of narrow definitions drawn from dominant Western-centric understandings of effective leadership (Weir, 2010). However, since these definitions are disconnected from their cultural contexts and cross-border implications, they can result in incongruities in their application, particularly in an Asian context (Harsanto & Roelfsema, 2015). The increasingly complex trading environment in this area would suggest that more focused research is needed to develop meaningful, respectful and relevant Halal sectorial leadership competency frameworks that successfully integrate the necessary socio-political values and cross-cultural complexities inherent in modern supply chains.